XXXV Lekkoatletyczne Mistrzostwa Polski Gdańsk 21-23 sierpień - 1959 / Miscewy. - Miscewy, Mieczysław (1927-2015). (Gdańsk : [s.n.], 1959)
Plakat z zawodów.
Keywords: Lekkoatletyka -- Polska -- Gdańsk -- 1945-1970 -- plakaty; Lekkoatletyka -- Polska -- 1945-1970 -- plakaty